THE FUNCTIONS OF FUND RAISING IN THE DEVELOPMENT OF STRATEGIC PLANNING PROCESS - Mahdi, Sahed (Universitas Muhammadiyah Aceh, 2008)
Artikel ini mendeskripsikan peran pentingnya strategi penggalangan dana dalam dunia perguruan tinggi yang dominan di praktekkan di Universitas Amerika dalam menbackup strategi pengembangan kampus. Kesuksesan dalam penggalangan dana juga di kaitkan dengan ketepatan strategi perencanaan yang di terapkan. Penelitian ini juga mendeskripsikan penerapan penerapan strategi terkini dalam penggalangan dana yang di implementasikan di berbagai perguruan tinggi Amerika, yang diharapkan bisa di terapkan di dalam pengembangan perguruan tinggi di Aceh. Hasil dari artikel ini, menyarankan para perencana strategis dalam dunia perguruan tinggi untuk mempertimbangkan ketersediaan dana terutama ketika memutuskan membangun kampus baru, penyediaan bantuan keuangan untuk mahasiswa, perekrutan dan mempertahankan dosen, dan menjamin terciptanya kesehatan keuangan yang stabil untuk masa depan kampus melalui penggalangan dana abadi. This article describes the importance of the role of fundraising strategies in the world of higher educations dominant practice at the American University in menbackup campus development strategy. Success in fundraising also associate with the precision planning strategies were implemented. The study also describes the implementation of the application of the latest in fundraising strategies being implemented at various American universities, which are expected to be applied in the development of universities in Aceh. The results of this article suggest the strategic planners in the worlds universities to consider the availability of funds, especially when deciding to build a new campus, providing financial aid for students, recruiting and retaining faculty, and ensuring the creation of a stable financial health for the future of the campus through perpetual fundraising . Keyword : strategic planning, fund raising, higher education. REFERENCES Associated Press (2008, October 31). UT Endowment fund takes 1 billion hit in financial crisis. Retrieved November 5, 2008 at http://www.chron.com/disp/story.mpl/front/6088139.html. A summary of best practice approaches in strategic planning processes. Retrieved May 2007 from http://www.cfar.com/Documents/-BestPract.pdf. Barlow, K. State money woes threaten cut in Pitt appropriation. University Times (41) 3. Bradburd, R.M. & Mann, D.P. (1993). Wealth in Higher Education Institutions. The Journal of Higher Education, 64, (4), 472-493. Breneman, D.W. Liberal arts colleges: thriving, surviving, or endangered? Washington, D.C.: The Brookings Institution, 1994. Chronicle of Higher Education (2008). Facts & Figures. College and University Endowments, 2007-2008. Retrieved November 5, 2008 at http://chronicle.com/premium/stats/endowments/results.php?year=2008&sort=market&stat Clotfelter, C. (2003). Alumni giving to elite private colleges and universities. Economics of Education Review, 22 (3). Cook, B. (1997). Fund raising and the college presidency in an era of uncertainty: from 1975 to the present. The Journal of Higher Education, 68 (1), 53-86. Cook, B. & Lasher, W.F. (1996). Toward a theory of fund raising in higher education. The Review of Higher Education, 20, (1), 33-51. Ehrenberg, R.G. (2002). Reaching for the bras ring: the U.S. News & World Report Rankings and competition. The Review of Higher Education, 26 (2), 145-162. Frey, D. (2002). University endowment returns are underspent – Higher Education-Statistical Data Included. Challenge, 43 (4), 109-121. Golden, D. (2007, March 2). Math lessons: to boost donor numbers, colleges adopt new tricks; sinking alumni stats, zeal for rankings spur rate inflation. Retrieved November 11, 2008. The Wall Street Journal. pp. A1. Harvard University web site. Retrieved November 8, 2008 at http://www.president.harvard.edu/speeches/faust/080424_openspaces.html Harvard University web site. Retrieved November 8, 2008 at http://hms.harvard.edu/public/strategy/21Mar2008.shtml. Liefner, I. (2003). Funding, resource allocation, and performance in higher education systems. Higher Education, 46 (4), 469-489. Majka, D. Presentation to University of Pittsburgh graduate class: Strategic Planning in Higher Education. Presented on November 10, 2008. Massy, W.F. (1994). Measuring Performance: How colleges and universities can set meaningful goals and be accountable. In ASHE Reader on Planning and Institutional Research. (pp.378-392): Peterson’s Guides: Princeton: New Jersey. Morrison, J.L. & Wilson, I. Analyzing environments and developing scenarios in uncertain times. Retrieved May 2007 from http://horizon.unc.edu/courses/papers/JBChapter.html. Office of Institutional Advancement, University of Pittsburgh. Campaign Update, Electronic Mail, received November 5, 2008 at http://ia-campaignupdate.createsend2.com/t/1/e/qlto/ilatryk/. Okunade, A.A. (1996). Graduate school alumni donations to academic funds: Micro-data evidence. American Journal of Economics and Sociology, 55, 213-229. Peterson, M. Using contextual planning to transform institutions. In M.W. Peterson, D.D. Dill, and L.A. Mets (Ed.), (1997) Planning and Management for a Changing Environmnet, Jossey-Bass. Ridley, D.R. & Boone, M.M. (2001). Alumni loyalty: A survey investigation. Reports-Research (143). Virginia Wesleyan College. Samuelson, R.J. (1967). Yale launches marathon campaign. Science, New Series, 158 (3809), 1658-1659. Schmidtlein, F. A., & Milton, T. H. (2000). College and university planning: Perspectives from a nation-wide study. In M. W. Peterson (Ed.), ASHE Reader on Planning and Institutional Research (pp. 107-119): Pearson Custom Publishing. Schworm, P. Harvard’s endowment surpasses 34 billion. Stock market fuels investment gains for elite colleges and universities. Retrieved November 5, 2008 at http://www.boston.com/news/local/articles/2008/01/24/harvards_endowment_surpasses_3 The Boston Globe. Strategic Planning in Higher Education: A Guide for Leaders. The State University of New Jersey, Rutgers. Department of University Relations. RU-0304-0296/1M. Strout, E. (2007) What’s the Big Idea? Chronicle of Higher Education (22), A21 The strategic planning process. Retrieved May 2007 from http://www.netmba.com/strategy/process/. University of Pittsburgh 2008 Fact Book. Retrieved October 28, 2008 at www.ir.pitt.edu/factbook/fbweb08.pdf. University of Pittsburgh Office of Student Life Retrieved November 11, 2008 at http://www.sorc.pitt.edu/ University of Pittsburgh Periodic Review Report. Retrieved October 8, 2008. Presented by Chancellor Mark A. Nordenberg to Middle States Commission on Higher Education, June 1, 2007. U.S. Department of Education, Strategic Plan for Fiscal Years 2007-12, Washington, D.C., 2007. Van Der Werf, M. (2007, May). Rankings methodology hurts public institutions. The Chronicle of Higher Education (53) 38, A13. Virginia Polytechnic Institute and State University web site. Accessed on September 1, 2008 at http://www.president.vt.edu/-strategicplan/. Whitely, M. A., Porter, J. D., Morrison, J. L., & Moore, N. (2000). Developing Scenarios: linking environmental scanning and strategic planning. In M. W. Peterson (Ed.), ASHE Reader on Planning and Institutional Research (pp. 107-119): Pearson Custom Publishing. World of Giving. (Fall, 2008). Campaign Update. Department of University Marketing Communications.